Návrh a realizace chytré domácnosti pro obytný vůz - Václavík, Marek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práce se zaměřuje na návrh a tvorbu systému chytré domácnosti pro specializované prostředí obytné dodávky. Tato práce zahrnuje teoretická východiska, analýzu zadání a současné situace společnosti a návrh výsledného systému. Návrh tohoto systému je vytvářen s ohledem na požadavky zadávající společnosti a informace získané pomocí analýz. Z těchto důvodu je výsledný systém vytvořen na základě open-source platformy Home Assistant.

This thesis focuses on the design and development of a smart home system for a specialized residential van environment. This thesis includes the theoretical background, analysis of the assignment and the current situation of the company and the design of the resulting system. The design of this system is created by considering the requirements of the assigning company and the information obtained through the analysis. For these reasons, the final system is based on the open-source platform Home Assistant.
Design and Implementation of Smart Home for Camper Van
Keywords: chytrá domácnost; domácí automatizace; Home Assistant; Raspberry Pi; Jinja2; YAML; návrh; analýza; HA; aplikace; Nabu Casa; Google asistent; smart home; home automation; Home Assistant; Raspberry Pi; Jinja2; YAML; design; analysis; HA; apps; Nabu Casa; Google Assistant